2020
DOI: 10.31933/dijms.v1i4.194
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Information System to Improve Employee Performance

Abstract: Today employee performance is a fundamental element for the progress of the institution. Along with the changing times demanded in increasing employee performance in order to achieve the objectives to be achieved. The discussion of this study regarding the decline in employee performance is characterized by a decrease in the percentage of achievement of work program targets. In this study, there are two variables, namely human resources information system variable (X) and employee performance variable (Y). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Therefore, how the human resource information systems is configured will help the organisation reap the most. Hikmawan & Santoso's (2020) [8] found that human resource information systems help support and better the organization. For instance, if human resources information systems are unclear in the same industry, then performance will not be realized any faster.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how the human resource information systems is configured will help the organisation reap the most. Hikmawan & Santoso's (2020) [8] found that human resource information systems help support and better the organization. For instance, if human resources information systems are unclear in the same industry, then performance will not be realized any faster.…”
Section: Discussionmentioning
confidence: 99%
“…On their side, employees are now used to technology and user experiences in their personal lives, and they want to bring it to the workplace. (Hikmawan & Santoso, 2020) described HRIS as "a system typically comprising one or more interrelated databases that track specific employment information".…”
Section: The Evolution Of Hrismentioning
confidence: 99%
“…This situation necessitates the modernization and digitization of the HR function. The HRIS is the tool that meets the needs of HR; digital processes, simplified, automated, and fast administrative tasks (Hikmawan & Santoso, 2020). It is a tool that will reconcile technical advances and the maturity of the HR function in a company.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these three exogenous variables that affect SHRCM, there are many other variables that influence it, including: a) Leadership: (Saputra & Mahaputra, 2022), (Sudiantini & Saputra, 2022), (Lavena & Lo, 2020), (Christian, Suroso, & Untari, 2022), (Gunawan, Suroso, & Syarief, 2022). b) Employee Perceptions: (Irdaningsih, Parwoto, & Badawi Saluy, 2020), (Hikmawan & Santoso, 2020), (Sianipar, 2022), (Harahap & Ali, 2020), (Gunawan et al, 2022). c) Job Satisfaction: (Haitao, 2022), (Eka & Anik, 2020), (Pamungkas, Iqbal, M, & Saluy, 2022), (Wydyanto & Yandi, 2020), (Khaira, Saputra, & Syarief, 2022).…”
Section: Conceptual Frameworkmentioning
confidence: 99%